Application of Girdling for Improved Fruit Retention, Yield and Fruit Quality in Syzygium samarangense under Field Conditions - Khandaker, M.M.; Boyce, A.N.; Osman, Normaniza; Hossain, A.S. (2011)
The study was undertaken to investigate the effects of different girdling techniques on the yield and quality of wax jambu fruits (Syzygium samarangense). Physiological and biochemical parameters were monitored at one week intervals during the three successive growth period from January, 2009 to May, 2010, using I-25%, C, V shaped, I-50% and 100% girdling. Girdling was applied three weeks before flowering every season. It was observed that the C-shaped girdling technique significantly enhanced the inflorescence development and produced the best results with regard to the fruit retention, fruit size, leaf chlorophyll and drymatter in comparison to the control and the other girdling techniques employed. Furthermore, C-shaped girdling enhanced faster fruit growth producing the best final fruit length and diameter, in addition to significantly increased number of fruits and mean fruit weight. It was also observed that I-50% girdling increased the L\D ration of fruit. I-shaped girdling increased the photosynthetic yield and dry matter content in the fruits compared to the control. With regard to fruit quality, the application of C-shape girdling increased total sugars, total phenolics and anthocyanins content in the fruits by 87, 28 and 138%, respectively compared to the control treatment. V-shape girdling increased the total flavonoids 150% more than control fruits. Girdling practices increased the antioxidant activity in the fruits. From this study, it can be concluded that girdling applied before flowering enhanced inflorescence development, increased yield and quality of wax jambu fruits under field conditions. (C) 2011 Friends Science Publishers